EVALUATION OF RESPONSE PANELIST ABILITY SOLUTION OF YOUNG PINEAPPLE IN CLUMPING MILK PROTEIN INTO MILK TOFU - K. S, AMALIA; MIWADA, N. S.; LINDAWATI, S. A. (Majalah Ilmiah Peternakan; Vol 26 No 2 (2023): Vol. 26 No. 2 (2023), 2024)
This study aims to evaluate the response of the panelists to milk tofu with the use of a natural coagulation agent, namely young pineapple juice. The study was conducted using a completely randomized design (CRD) with four treatments and four replications. Each replication using 1000 ml of cow milk, the four treatments were adding 30cc of pineapple juice (P1), adding 40cc of pineapple juice (P2), adding 50cc of pineapple juice (P3), and adding 60cc of pineapple juice (P4). The observed variables were the hedonic test for the level of preference and the sensory quality test, namely color, taste, scent, elasticity and overall acceptance. The results of this study indicated that the manufacture of milk tofu using natural coagulation ingredients of young pineapple juice (Ananas comosus) from all variables (color, taste, scent, elasticity, and overall acceptance) and each treatment (P1, P2, P3, P4) showed that the results were significantly different (P<0.05). The hedonic test value (preferred level) on color, taste, scent, and overall acceptance was highest in P1 with a sequential value of 4.12; 4.16; 4.08; and 3.88, while the highest value for elasticity was found at P3. The conclusion of this study can be suggested using 30 cc of young pineapple juice as a natural coagulation material in the manufacture of milk tofu because it produces milk tofu with a milky white color, the scent of cow milk, a slightly chewy texture, and a slight milk taste.